Applied Inorganic Chemistry. From Construction Materials to Technical Gases - Behrend, Detlef; Behrens, Rainer; Bertau, Martin; Boos, Markus; Broll, Sascha; Buchner, Magnus; Dewalsky, Martin V.; Eckert, Hellmut; Engel, Stefan; Feser, Ralf; Fickenscher, Thomas; Janka, Oliver; et al. (De Gruyter Textbook, 2022)
Many elements and inorganic compounds play an extraordinary role in daily life for numerous applications, e. g., construction materials, inorganic pigments, inorganic coatings, steel, glass, technical gases, energy storage and conversion materials, fertilizers, homogeneous and heterogeneous catalysts, photofunctional materials, semiconductors, superconductors, soft- and hard magnets, technical ceramics, hard materials, or biomedical and bioactive materials. The present book is written by experienced authors who give a comprehensive overview on the many chemical and physico-chemical aspects related to application of inorganic compounds and materials in order to introduce senior undergraduate and postgraduate students (chemists, physicists, materials scientists, engineers) into this broad field. Volume 1 covers construction materials, coatings, metals, intermetallics, technical glasses and technical gases. Vol. 2. From Energy Storage to Photofunctional Materials. Vol. 3. From Magnetic to Bioactive Materials.